Trends in hospital admissions for obstructive lung disease from 2000 to 2010 in Portugal. (July 2016) - Vieira, Rafael; Fonseca, João Almeida; Lopes, Fernando; Freitas, Alberto
Abstract: The burden of hospitalisations for obstructive lung diseases (OLD) has not been sufficiently studied. We aimed to characterise the hospitalisations for OLD from 2000 to 2010 in all Portuguese public hospitals. We analysed hospital discharges with a diagnosis of OLD regarding the patients' gender, age, residence and comorbidities. Of the 120 399 hospital admissions with a principal diagnosis of OLD, COPD (ICD-9-CM 491.x, 492.x, 496) was responsible for 81%. The change in patients discharged with OLD as a principal diagnosis was only 1% from 2000 to 2010 and did not change for COPD. Hospital admissions and deaths for COPD and other OLD increased with age and were more common in men than women. In-hospital mortality for COPD decreased 34.1% from 2000 to 2010, while the median length of stay was fairly constant at 8 days. Respiratory failure, insufficiency and/or arrest, and pneumonia, are the principal diagnoses often associated with COPD. When both pneumonia and COPD were diagnosed there was an increasing trend to classify pneumonia as the principal diagnosis (64.4%–72.9%), a sign that may lead to underestimation of COPD hospitalisations. In summary, a considerable decrease in in-hospital COPD mortality was observed while hospital admissions and the length of stay did not change substantially. These results suggest that better healthcare or other factors may be counteracting the expected increase of the burden of COPD. Highlights: COPD is responsible for over 80% of hospital admissions for OLD. From 2000 to 2010, hospitalisations with COPD as principal diagnosis did not increase. Mortality for COPD and OLD has decreased, but length of stay did not change. COPD is often a comorbidity in respiratory failure and pneumonia hospitalisations. There was an increasing trend to disfavour COPD over pneumonia as principal diagnosis.